Loneliness and its association with physical health conditions and psychiatric hospitalizations in people with serious mental illness. Issue 5 (2nd September 2020) - Fortuna, Karen L.; Brusilovskiy, Eugene; Snethen, Gretchen; Brooks, Jessica M.; Townley, Greg; Salzer, Mark S.
ABSTRACT: This study explored the association between loneliness and psychiatric hospitalizations, functioning, and physical health conditions in people with serious mental illness. Data were included from 349 individuals with serious mental illnesses, aged 18+ years, who participated in two consecutive cross-sectional survey studies conducted between 2013 and 2018. This study found a higher number of psychiatric hospitalizations in the past 6 months were associated with greater loneliness. The Short-Form-12 mental component score was a highly significant correlate, accounting for a significant amount of variance in loneliness scores. The physical component score and the bodily pain subdomain of the Short-Form-12 were also significantly associated with loneliness, with individuals with lower physical functioning and greater bodily pain reporting more loneliness. Having a higher total number of health conditions, a higher total number of conditions that cause pain, and the presence of at least one respiratory condition were found to be associated with greater loneliness. Loneliness may be an important dimension of health as related to health conditions associated with pain, functioning, and psychiatric hospitalizations among people with serious mental illness. These findings reinforce the powerful role of socio-cultural and environmental factors in shaping whole health in people with serious mental illness.